Hidrogeradora virtual: utilização de técnicas de realidade virtual desktop para o estudo de uma unidade hidrelétrica de energia - PAMPLONA JUNIOR, Alcides Renato da Silva (Universidade Federal do Pará, 2017)
This dissertation presents the conception, project and implementation of an educational environment that uses Virtual Reality Desktop techniques for study of an industrial plant. The application uses CAD models of plants constituent parts, hierarchically organized having as database documents in XML format. It also presents a textual area through which trainee receives information on what is being shown in virtual world. For case study the plant of a Hydroelectric Generating Unity is used.